Perancangan Ulang Rumah Sakit Ibu Dan Anak Melinda Bandung Dengan Pendekatan Psikologi Ruang - Salsabila, Dita; Faza Surya Rusyda, Hana; Sri Ismiranti, Athifa (Telkom University, 2024)
The public's perspective on hospitals is often associated with a negative atmosphere, such as being frightening, making it important to change this image to support both psychological and physical healing processes. The goal of the redesign of the Melinda Mother and Child Hospital in Bandung is to create an environment that caters to the psychological needs and comfort of users, particularly the people of Bandung, while they are at the hospital. The design process involved methods such as observation, interviews, questionnaires, documentation, and literature review. The hospital was redesigned using a spatial psychology approach, with the theme